Development and Application of a Chemical Labeling‐Based Biosensing Assay for Rapid Detection of 8‐Oxoguanine and Its Repair in vitro and in Human Cells. Issue 19 (26th July 2022) - Kong, Weiheng; Ji, Yongqin; Zhu, Xiaowen; Dai, Xiaoxia; You, Changjun
Comprehensive Summary: Living cells are constantly threatened by endogenous and environmental agents that can induce various DNA lesions including 8‐oxoguanine (8‐oxoG). Increasing evidence has suggested that 8‐oxoG is not only a biomarker of oxidative stress, but also a novel epigenetic‐like modification involved in transcriptional regulation in mammalian cells. Measurement of DNA damage and repair is useful for both basic research and clinical applications, but current methods for 8‐oxoG detection still suffer from some problems such as poor selectivity, time consuming and being expensive. Here, we developed a fast and simple biosensing approach for quantitative analysis of 8‐oxoG in DNA, which was based on the selective chemical biotinylation of 8‐oxoG in conjunction with biotin‐streptavidin enzyme‐linked immunosorbent assay. We have also successfully applied this method to achieve efficient detection of the repair activities of DNA glycosylases Fpg and hOGG1 toward 8‐oxoG in vitro and in human cells. This newly developed biosensing assay should be generally applicable for rapid detection of 8‐oxoG and its repair in other organisms. Abstract : A fast and simple biosensing approach was developed for quantitative analysis of 8‐oxoG in DNA, which was based on the selective chemical biotinylation of 8‐oxoG in conjunction with biotin‐streptavidin enzyme‐linked immunosorbent assay. This newly developed biosensing assay should be generally applicable for rapid detection of 8‐oxoG and its repair in organisms.